A Study of Customer Satisfaction Towards Imika Muar - RAJAB, NAJIHA AZWA; SUFAHANI, PROF. MADYA Ts. DR. SULIADI FIRDAUS (Enhanced Knowledge in Sciences and Technology, 2024)
In this economic growth of Malaysia, refurbished laptops and other electronic devices have assumed high in demand because most of educations need to do assessment which using laptops. Thus, this study helps one of company which provides refurbished laptops in all around Malaysia region. Firstly, this study is to collect insights of customer walked in behavior, preferences, and feedback to Imika Muar by implementing a questionnaire. Secondly, this study is to analyze satisfaction index of customer towards Imika Muar. Thirdly, this study is to identify the most influence factors that affects the increasing number of customers by applying survey analysis. This study involving the method of satisfaction index, simple survey analysis and crosstabulation in order to analyse the data obtained. The satisfaction index is used to estimate the score of customer satisfaction. Next, the crosstabulation and survey analysis are used to analyse the data of customer satisfaction to find out the most influence factors that affects the increasing number of customers. The result shows that the satisfaction index is 71.0% and it is fairly enough showing customer satisfied but the company need to increase it more because there are many competitors around. For the survey analysis shows result for different section such as demographic and soci-economic finding, customer awareness, purchase behavior, product references, quality perception, service experience, future experience, and satisfaction which is mentioned in result and discussion of this paper. This study also shows that the finding of crosstabulation is highly depends on word-of-mouth for the customer discovering Imika Malaysia. For further research may focus on the depth study of satisfaction index of customer satisfaction in Imika Muar for a longer period of time.